Effect of seed rate on yield and proximate constituents of different parts of hydroponics maize fodder - NAIK, P K; SWAIN, B K; CHAKURKAR, E B; SINGH, N P (The Indian Journal of Animal Sciences, 2017)
A study was conducted to find out the effect of seed rate (3.8, 5.1, 6.4, 7.6, 8.9 and 10.2 kg/m2) on the yield and proximate constituents of different parts of the hydroponics maize fodder (HMF) produced in a hydroponics chamber (greenhouse) measuring about 25 ft length × 10 ft width ×10 ft height with a daily production potential of 600 kg fresh HMF; and equipped with automatic sprayer irrigation of tap water. The HMF looked like a mat of 20-30 cm height consisting of roots along with germinated seeds and leaves. The total yields (kg) of the HMF both on fresh basis (4.94-4.97) and DM basis (0.67-0.64) were similar and higher with a seed rate of 3.8 to 7.6 kg/m2. The yield (kg, as % of total yield) of the leaves on fresh basis (1.67-1.60, 31.59-32.49) and DM basis (0.11, 16.33-16.99) was similar and higher with a seed rate of 5.1 to 7.6 kg/m2. The fresh yield (kg) of the roots along with the germinated seeds increased with the increase in the seed rate. The yield (as % of total yield) of the roots with the germinated seeds on fresh basis remained similar up to seed rate of 8.9 kg/m2 (67.51-69.26) and increased at the seed rate of 10.2 kg/m2 (72.57). The seed rate had no effect on the proximate constituents of different portions i.e. roots with germinated seeds, leaves and plants of HMF. However, irrespective of the seed rate, there was difference in the proximate constituents of roots with germinated seeds, leaves and plants of HMF. The HMF had highest moisture content in the roots (15.68%) and lowest in the leaves (6.81%). The CP, CF and TA contents (%) of the HMF were highest in the leaves (22.15, 17.69 and 3.84) and lowest in the roots (10.25, 9.76 and 1.59). The EE content of the leaves (2.90%) was similar with the roots (3.01%) and plants (2.29%), however, the roots and plants were different. It can be concluded that the seed rate had no effect on the proximate constituents of different portions i.e. roots with germinated seeds, leaves and plants of the HMF. The seed rate of 7.6 kg/m2 can be recommended for the production of hydroponics maize fodder for optimal output and all parts of the hydroponics maize fodder are nutritious.